2020
DOI: 10.1093/ijnp/pyaa081
|View full text |Cite
|
Sign up to set email alerts
|

Serotonin Transporter Gene Promoter Hypomethylation as a Predictor of Antidepressant Treatment Response in Major Depression: A Replication Study

Abstract: Background The serotonin transporter gene (SLC6A4; 5-HTT; SERT) is considered a prime candidate in pharmacogenetic research in major depressive disorder (MDD). Besides genetic variation, recent advances have spotlighted the involvement of epigenetic mechanisms such as DNA methylation in predicting antidepressant treatment response in “pharmaco-epigenetic” approaches. In MDD, lower SLC6A4 promoter methylation has been suggested to predict impaired response to serotonergic antidepressants. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
20
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(24 citation statements)
references
References 61 publications
(30 reference statements)
2
20
0
Order By: Relevance
“…Our study showed a signi cant correlation between SLC6A4 methylation and AN, which was in concordance with the observation in patients with depression [39,40]. Probably because SLC6A4 hypermethylation causes the decrease of mRNA expression, which leads to the decrease of 5-HT transporter protein and 5-HT reuptake, then resulting in the increase of 5-HT concentration in synaptic space and the decrease of 5-HT synthesis by negative feedback, nally it may increase the e cacy of serotonergic antidepressants [41]. While previous studies did not nd positive results in ANs [42,43], which may be due to the differences in the samples and fragments selected.…”
Section: Discussionsupporting
confidence: 84%
“…Our study showed a signi cant correlation between SLC6A4 methylation and AN, which was in concordance with the observation in patients with depression [39,40]. Probably because SLC6A4 hypermethylation causes the decrease of mRNA expression, which leads to the decrease of 5-HT transporter protein and 5-HT reuptake, then resulting in the increase of 5-HT concentration in synaptic space and the decrease of 5-HT synthesis by negative feedback, nally it may increase the e cacy of serotonergic antidepressants [41]. While previous studies did not nd positive results in ANs [42,43], which may be due to the differences in the samples and fragments selected.…”
Section: Discussionsupporting
confidence: 84%
“…Our study showed a signi cant association between SLC6A4 methylation and AN, which was in concordance with the observation in patients with depression [26,27]. Probably because SLC6A4 hypermethylation causes the decrease of mRNA expression, which leads to the decrease of 5-HT transporter protein and 5-HT reuptake, then resulting in the increase of 5-HT concentration in synaptic space and the decrease of 5-HT synthesis by negative feedback, nally it may increase the e cacy of serotonergic antidepressants [28]. While previous study did not nd positive results in AN patients [29], which may be due to the differences in the samples and fragments selected.…”
Section: Discussionsupporting
confidence: 84%
“…Considering the possible effect of 5-HTTLPR methylation on long-term AN outcome, some studies have reported the predictive effect of 5-HTTLPR methylation on the therapeutic response in depression patients, the higher the 5-HTTLPR methylation level, the better the antidepressant response [28,33], but there were also contrary results [34], as for how gene methylation affects the therapeutic effect has not been reported. It was the methylation level of CpG11 unit in 5-HTTLPR that was signi cantly associated with therapeutic responses [35].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…As these factors are highly variable, epistatic, and complex, they are thought to regulate vulnerability to depression development and responsiveness to antidepressant therapy. Various polymorphisms have been reported in genes regulating the hypothalamic-pituitary-adrenal (HPA) axis, serotonin recycling, and immune responses, including corticotropin-releasing hormone receptor 1, the sodium-dependent serotonin transporter gene (SLC6A4), and interleukin-1β (IL-1β) (Baune et al, 2010;Schiele et al, 2021). Moreover, environmental stressors are associated with epigenetic modification of BDNF, its receptor tropomyosin-related kinase B gene, glucocorticoid receptor gene (NR3C1), and glutamate ionotropic receptor NMDA type subunit 2B (GRIN2B) (Ernst et al, 2009;Jiang et al, 2010;Sun et al, 2013;Efstathopoulos et al, 2018).…”
Section: Neuroinflammation In the Pathophysiology Of Depressionmentioning
confidence: 99%